Becoming a visible man - Green, Jamison, 1948- (Book collections on Project MUSE., 2020)
"Leading transsexual activist Jamison Green combines candid autobiography with informed analysis to offer unique insight into the multiple challenges of the female-to-male transsexual experience, ranging from encounters with prejudice and strained relationships with family to the development of an FTM community and the realities of surgical sex reassignment. Offers recollections of Green's own experiences-including his childhood struggles with identity and his years as a lesbian parent prior to his sex-reassignment surgery; examines transsexualism as a human condition, and sex reassignment as one of the choices that some people feel compelled to make in order to manage their gender variance. The 2nd edition has been thoroughly revised, updated, and expanded to reflect political, cultural, and linguistic changes as well as concerns and issues that have developed since the original text was published in 2004"--